A DESCRIPTIVE STUDY OF DIDACTIC COMMUNICATION - CRISTIAN STAN (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. The efficiency of didactic communication largely determines both the quality of the educational process as well as the preparedness of the students. Given this starting point, our study primarily aims to investigate students' opinions on the quality of didactic communication. The main investigative methods used were the semi-structured interview and the questionnaire based survey with the focus on items such as: the extent and conditions under which students appreciate didactic communication as being effective, indicators that students consider that didactic communication is effective, factors that generate a sense of satisfaction as a result of attending a course and communication blockages. The results of the investigation indicate the fact that most subjects recommend devoting more attention to defining and explaining the fundamental concepts for overcoming communicational blockages.